2022
DOI: 10.1021/acsami.2c02803
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of Boron Nitride as a Large-Scale Passivation and Protection Layer for Two-Dimensional Materials and High-Performance Devices

Abstract: Two-dimensional materials (2DMs) with extraordinary electronic and optical properties have attracted great interest in optoelectronic applications. Due to their atomically thin feature, 2DM-based devices are generally sensitive to oxygen and moisture in ambient air, and thus, practical application of durable 2DMbased devices remains challenging. Here, we report a novel strategy to directly synthesize amorphous BN film on various 2DMs and field-effect transistor (FET) devices at low temperatures by conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…As an alternative for the crystalized h-BN, amorphous boron nitride (a-BN) has been considered a promising encapsulating material for 2DMs because it is relatively free of defects (traps and dangling bonds) and requires low growth temperature. 26 31 Glavin et al and Hong et al explored the dielectric properties of ultrathin a-BN film and diffusion barrier behavior for ultrathin electronic devices. 28 , 29 Uddin et al confirmed that FETs of graphene on an a-BN heterointerface could enhance the hole and electron mobilities to 4980 and 4200 cm 2 /Vs, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As an alternative for the crystalized h-BN, amorphous boron nitride (a-BN) has been considered a promising encapsulating material for 2DMs because it is relatively free of defects (traps and dangling bonds) and requires low growth temperature. 26 31 Glavin et al and Hong et al explored the dielectric properties of ultrathin a-BN film and diffusion barrier behavior for ultrathin electronic devices. 28 , 29 Uddin et al confirmed that FETs of graphene on an a-BN heterointerface could enhance the hole and electron mobilities to 4980 and 4200 cm 2 /Vs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Very recently, Lu et al verified that a-BN film successfully suppresses current fluctuations and enhances carrier mobility of 2D materials. 31 However, fabricating a-BN films still has several issues, such as the requirement of additional annealing processes at relatively high temperatures, complicated processes for making the protection layer, and the debate over the transfer process. Above all, experiments to confirm whether a-BN can sufficiently protect 2D materials from the external environment and help improve electrical performance have not been appropriately explored or performed yet ( Table S2 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations